Diagnostic Performance of ESR in Automatic Hematologic Analyzer Mindray BC-760 Compared with CRP to Detect Inflammation in The Adult Population - Ratnaningsih, Tri; Donytra Arby Wardhana (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
C-reactive protein (CRP) is considered a more reliable inflammatory marker than the erythrocyte sedimentation rate (ESR). However, ESR remains widely used in clinical practice. Westergren is the most common method for ESR analysis, although it has limitations, including a long processing time and a requirement for a high blood volume. Currently, an automatic hematologic analyzer has been developed that simultaneously examines ESR. This study aims to evaluate the diagnostic performance of ESR in the automatic hematologic analyzer Mindray BC-760 compared to CRP. A Total of 489 adult participants who were admitted to medical check-ups were recruited in this Cross-sectional observational study. Data were further analyzed using SPSS version 26. The median age was 30 years (range, 24-50 years). The participants were further divided into two groups: those with low CRP (<5 mg/L) and those with high CRP (≥5 mg/L). ESR was significantly elevated in the high CRP group, 14.05 (0.21-48.78) mm/h, compared to the low CRP group, 7.5 (0.27-33.84) mm/h, p <0.001. ESR showed a positive correlation with CRP when Spearman's correlation test was performed (r = 0.338; p <0.001). The diagnostic performance of automatic ESR was further analyzed by referring to Westergren's normal range, which takes into account gender differences (male: <15 mm/h; female: <20 mm/h). In the male group, the AUC was 0.707 (p <0.001), specificity 96.5%, sensitivity 21.1%, likelihood ratio LR +5.95, and LR -0.82. In the female group, the AUC was 0.706 (p <0.001), specificity 83.1%, sensitivity 46.3%, LR +2.73, and LR -0.65. The ESR test using the automatic hematologic analyzer Mindray BC-760 showed moderate diagnostic performance in both the adult male and female groups.